2022
DOI: 10.21203/rs.3.rs-1836546/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of optimal gestational weight gain for twin pregnancy in Southwest China: a retrospective study

Abstract: There is a lack of data on gestational weight gain (GWG) in twin pregnancies. We divided all the participants into two subgroups: the excellent outcome subgroup and the adverse outcome subgroup. They were also stratified according to prepregnancy body mass index (BMI): underweight (< 18.5 kg/m2), normal weight (18.5–23.9 kg/m2), overweight (24–27.9 kg/m2), and obese (≥ 28 kg/m2). We used 2 methods to confirm the optimal range of GWG. The first method was a statistical-based method (the interquartile range o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, chronic hypertension during twin pregnancies have been shown to increase the risk of GDM [22,23]. Previous studies have shown that gestational weight gain during twin pregnancies in China ranges from 15 to 21 kg [20,21]. Excessive gestational weight gain has also been identified as a risk factor for hypertensive complications during pregnancy [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, chronic hypertension during twin pregnancies have been shown to increase the risk of GDM [22,23]. Previous studies have shown that gestational weight gain during twin pregnancies in China ranges from 15 to 21 kg [20,21]. Excessive gestational weight gain has also been identified as a risk factor for hypertensive complications during pregnancy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-pregnancy BMI[19]: Underweight, BMI < 18.5; normal weight, 18.5 ≤ BMI < 24; overweight, 24 ≤ BMI < 28; obesity, BMI ≥ 28. (2) Excessive gestational weight gain[20,21]: Total weight gain (TWG) or gestational gain BMI (GWGR) exceeded the established standards: underweight and normal weight, TWG ≥ 21 kg or GWGR ≥ 0.58; overweight, TWG ≥ 20 kg or GWGR ≥ 0.55; obesity, TWG ≥ 18 kg or GWGR ≥ 0.50. (3) Preterm birth: before 34 or 37 complete weeks of gestation.…”
mentioning
confidence: 99%